Development of the narrative and argumentative analysis as a NDP’s ideas diffuser: a gaze to education (2015)
In the current research is made an analysis which pretends to evaluate the form and essence of the previous five National Development Plans (NDP), where there are expressed the objectives and projects of the political, legal, economic and social nature of the country. In this study are analyzed the syntactic and semantic macrostructure that only correspond to the education approach, taking a set of variables that allow the potential of argumentative, grammatical, economic and political aspects. In order to understand the whole textual superstructure it is segmented the research and the analysis; this division will be called ‘surfaces’, concluding with three of them. Each surface was analyzed by different sorts of variables, which have the function of observing specific aspects.